A rare Pb9 cluster-organic framework constructed from a flexible cyclotriphosphazene-functionalized hexacarboxylate exhibiting selective gas separation. Issue 9 (28th July 2017) - Bai, Dongjie; Chen, Fengli; Jiang, Donghao; He, Yabing
Abstract : A rare Pb9 cluster-based organic framework constructed from a flexible cyclotriphosphazene-functionalized hexacarboxylate exhibits selective adsorption separation of C2 hydrocarbons and CO2 from CH4 under ambient conditions. Abstract : It is quite challenging to fabricate metal–organic frameworks with permanent porosity using flexible organic ligands owing to their conformation freedom and flexibility making the resultant frameworks very difficult to stabilize. Successful synthesis of such frameworks will enrich the domain of porous compounds for various applications. In this work, we designed a flexible cyclotriphosphazene-functionalized hexacarboxylate, and used it to successfully construct a porous metal–organic frameworkZJNU-62 upon solvothermally reacting with Pb 2+ ions. Single-crystal X-ray diffraction analyses show thatZJNU-62 is composed of nonanuclear Pb9 clusters connected by organic linkers to form a (4, 12)-connected three-dimensional infinite network of Al3 La topology with one-dimensional rectangular channels running along the crystallographic c axis. Although the organic ligand is flexible, the resulting MOF compoundZJNU-62 can sustain the desolvation and exhibit permanent porosity, which has been confirmed by various gas adsorption isotherms. In particular, this compound can selectively adsorb C2 hydrocarbons and CO2 from methane under ambient conditions, indicating its promising potential for natural gas purification. The predicted IAST adsorption selectivities are 21.0, 10.9, 13.2 and 5.8 for the equimolar C2 H2 /CH4, C2 H4 /CH4, C2 H6 /CH4 and CO2 /CH4 gas mixtures at 298 K and 100 kPa, respectively. This work represents a rare example of a Pb-based MOF constructed from a flexible organic ligand exhibiting selective gas adsorption properties.